1991
DOI: 10.1063/1.104696
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of electro-optic response in poled polyimide systems

Abstract: Using polyimide as host in a guest-host thin film we demonstrate the first poled-polymer electro-optic response stable at temperatures up to 150 °C (samples poled and cured at 250 °C). A coplanar-electrode poling geometry is used so that the molecular alignment of the guest dye between the electrodes is coincident with the free volume of the host. We hypothesize that ‘‘high’’ temperature poling during the imidization process, when the polyimide forms rings and densifies, accounts for the excellent poled respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(75 citation statements)
references
References 6 publications
1
73
1
Order By: Relevance
“…mer, cross-linked polymers, and dendrimeric structures. [8][9][10][11][12] Using supramolecular self-assembled molecular glasses, an EO coefficient as high as 327 pm/V was achieved, approximately ten times higher than LiNbO 3 , and showed 83% temporal alignment stability for 3 months at room temperature. 13 Noncentrosymmetric Langmuir Blodgett ͑LB͒ films with ͑2͒ values as large as 760ϫ 10 −9 esu have been fabricated, approximately four times larger than that of LiNbO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…mer, cross-linked polymers, and dendrimeric structures. [8][9][10][11][12] Using supramolecular self-assembled molecular glasses, an EO coefficient as high as 327 pm/V was achieved, approximately ten times higher than LiNbO 3 , and showed 83% temporal alignment stability for 3 months at room temperature. 13 Noncentrosymmetric Langmuir Blodgett ͑LB͒ films with ͑2͒ values as large as 760ϫ 10 −9 esu have been fabricated, approximately four times larger than that of LiNbO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the multitude of potential frequency conversion, optical modulation, and optical switching applications that stem from the (2) second-order susceptibility, several novel methods for creating noncentrosymmetric materials incorporating organic molecules with large ␤ molecular susceptibilities have been developed over the past decade. These include electric-field poled polymers, [1][2][3] Langmuir-Blodgett films, [4][5][6] and covalent selfassembled monolayer structures. [7][8][9] We report here detailed studies of a ionically self-assembled monolayer technique for the creation of noncentrosymmetric organic thin films with substantial (2) values.…”
mentioning
confidence: 99%
“…Wu et al have reported on an organic guest/host system where polyimide is used as the host [24]. They have demonstrated that EO response of the poled organic guest/host material is stable at relatively high temperatures (150 'C).…”
Section: Polyimide / Inorganic Systemmentioning
confidence: 99%